GERAK TARI KREASI LENGGANG SERAWAI: “KAJIAN BENTUK DAN GAYA” - Alfhina Wahyu Rahmadaniah; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to reveal the description of the form and movement style of the creative dance Lenggang Serawai. This research uses a qualitative approach with a descriptive method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data were collected through literature study, observation, interviews, and documentation. The steps to analyse the data are data collection, data reduction, data presentation, and drawing conclusions. The results show that the movements of Lenggang Serawai dance at Afnalya Dance Company can be reviewed from the aspects of form and style, which include the aspect of form such as types of movement, movement structure, the relationship between basic elements of space, time, and energy, as well as the aspect of style including unique movement characteristics and characteristic rhythmic patterns of movement. Based on the observed results, the Lenggang Serawai dance has 7 types of movement and 23 movement structures. The spatial aspects in the movements of the Lenggang Serawai dance include line, volume, direction of facing, and focus of gaze. The lines in this dance are predominantly straight, horizontal, and diagonal. The volumes in this dance are predominantly large and small. The directions of facing in the movements of the Lenggang Serawai dance are predominantly forward, backward, left side, and right side. The levels in the movements of the Lenggang Serawai dance are predominantly medium and high. The gaze focus in the movements of the Lenggang Serawai dance is predominantly forward, downward, towards the hands, towards the properties held, and to the left and right sides. In terms of time, the tempo and rhythm are predominantly medium. Regarding the energy aspect, the intensity in these dance movements is predominantly medium, the pressure in the dance movements is predominantly medium, and the movement quality of the Lenggang Serawai dance is predominantly medium.